Problems of Implementing the Islamic Religious Education (PAI) Integrated Education System Curriculum (Study of Analysis of the Combination of School Curriculum with the Manba'usshafa Islamic Boarding School, Pontianak Timur) - Faisal Abdullah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the problems of implementing the PAI Curriculum by combining the School Curriculum with Islamic Boarding Schools. This study uses a qualitative descriptive method. Based on the results of the research, the problems that occur in implementing the integrated education system PAI curriculum include: first problems related to teachers, because the majority of teachers do not yet have academic requirements as teachers, secondly related to students, because all students are required to study at school, so they are many who have difficulty adapting to the new environment, thirdly related to facilities, with incomplete supporting facilities, and fourthly funding problems, due to late contributions from students' parents each month for student meal costs and educational staff incentives.